A guide to parliamentary practice: A handbook - IPU, UNESCO (2003)
This Handbook constitutes a practical guide on parliaments and their methods of work. It is intended for use by the UNESCO Secretariat, including its Field Network of 57 field offices, and by the network of 190 National Commissions for UNESCO which act as the relay of the organisation’s activities in Member States and Associate members.